KEPADATAN BAKTERI Coliform DI SUNGAI SEGEDONG KABUPATEN PONTIANAK - Riza Linda, Akhmad Fathoni, Siti Khotimah, (Jurnal Protobiont, 2016)
Coliform bacteria are microbes which can be used as a biological indicator of pollution of the water especially the Eschericia Coli bacteria. The aim of this research is to find out the density of coliform bacteria in Segedong River, Pontianak Regency. The research was carried out from October 2012 until March 2013 atthe Segedong River, Pontianak Regency. The coliform bacteria were examined in three stages, i.e. presumtive tes comfirmative test, and data analysis which was conducted at the Laboratory of Microbiology, Faculty of Mathematics and Natural Sciences, Tanjungpura University Pontianak. The research findings showed that the bacterial density range was 3,65 X 105 MPN/ 100 ml to 8,81 X 105 MPN/100 ml when the water of the river rose, and 3,27 x 105 MPN/100 ml to 9,25 x 105 MPN/100 ml when the water of the river was low.